PHYSIOLOGICAL QUALITY OF PAPAYA SEEDS (CARICA PAPAYA L.) AS AFFECTED BY KNO₃ PRIMING AND STORAGE DURATION - Malik, Abi; Wartapa, Agus; Aziza, Elea Nur (RADJA PUBLIKA, 2025)
This study investigates the effects of KNO₃ priming timing and storage duration on the physiological quality of papaya seeds (Carica papaya L.). A factorial randomized block design was used with two factors: priming timing no priming (P0), priming before germination (P1), after seed extraction (P2), and after drying (P3); and storage duration 1 month (L1), 2 months (L2), and 3 months (L3). Observed parameters included growth uniformity, growth rate, vigor index, germination percentage, and maximum growth potential. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Results showed that priming before germination (P1) significantly improved growth uniformity and growth rate, while storage for two months (L2) yielded the best physiological seed quality in most parameters. A significant interaction was observed in the vigor index, with the best results from priming before sowing (P1) combined with 2–3 months of storage. The findings suggest that KNO₃ priming prior to germination and two months of storage is optimal for maintaining seed vigor and viability.